Superior anti-corrosion and self-healing bi-functional polymer composite coatings with polydopamine modified mesoporous silica/graphene oxide. (30th December 2021) - Ma, Yanqi; Huang, Haowei; Zhou, Hongda; Graham, Michael; Smith, James; Sheng, Xinxin; Chen, Ying; Zhang, Li; Zhang, Xinya; Shchukina, Elena; Shchukin, Dmitry
Highlights: BTA/MSNs-functionalized graphene oxide (fGO) was fabricated via in-situ polymerization of PDA in one pot. fGO nanocontainers shows good barrier property and high pH-sensitivity. fGO-based composite waterborne epoxy (WEP) coatings reveals superior anti-corrosion and self-healing performance. Abstract: In this article, graphene oxide (GO) and benzotriazole-loaded mesoporous silica nanoparticles (BTA/MSNs) are combined on micro scale through the in situ polymerization of polydopamine (PDA), preparing a self-healing bi-functional GO (fGO) used as nano-fillers for anti-corrosion enhancement of waterborne epoxy (WEP) coatings. Scanning electronic microscopy (SEM) images show that the BTA/MSNs are uniformly distributed on the surface of high aspect ratio GO nanosheets to endow GO nanocontainer characteristics. UV-vis profiles demonstrate that fGO has pH-controlled release function. Modulus at lowest frequency is generally used for comparing the corrosion resistance of organic coatings. Modulus at lowest frequency (1.42 × 10 7 Ω cm 2 ) after 30 days immersion in 3.5 wt.% NaCl solution revealed 2 orders of magnitude higher that of blank WEP (1.17 × 10 5 Ω cm 2 ). With artificial cracks on its coatings, fGO/WEP had no obvious rust compared with blank WEP after 240 h of immersion. We anticipate that self-healing and physical barrier bi-functional nanocontainers improve the traditional anticorrosion coating efficiency with better, longer-lasting performance for shipping, oil drilling or bridge maintenance. Graphical abstract: Image, graphical abstract